Corrosive effect of HCl and H2SO4 exposure on the strength and microstructure of lithium slag geopolymer mortars - Javed, Usman; Shaikh, Faiz; Sarker, Prabir (2024)
Resistance of geopolymer against aggressive effects of strong acid governs its service life. This research investigates the effect of silica fume incorporation on the strength degradation of lithium slag geopolymer (LSG) mortars after exposure to strong acids and presents the relationship between microstructure, calorimetry, and residual strength. Silica fume incorporated LSG mortars containing sodium (Na) and potassium (K) based alkaline activators were exposed to 5% sulphuric and hydrochloric acid solutions separately for 60 days. The sulphuric acid deterioration of LSG in terms of maximum percentage reduction in compressive strength was 37.42% upon incorporating 40% silica fume in geopolymer with a Na-based alkaline activator. LSG mixes activated by Na-activators demonstrated higher acid resistance compared to those activated by K-based activators. Leaching of aluminium (Al) from the aluminosilicate gel matrix occurred, which subsequently deteriorated aluminosilicate gel matrix when exposed to hydrochloric acid, whereas the leaching of Al occurs alongside the crystallization of calcium sulfate when specimens were exposed to sulphuric acid solution. The incorporation of silica fume reduces the initial calorimetric heat evolution and higher degree of geopolymerization marked by higher heat evolution between 5–48 h than the control LSG. The intense evolution of heat in control LSG at the initial stage of geopolymerization yielded a poor microstructure. Thus, acid-induced strength degradation is lower in silica fume-incorporated gel due to its denser microstructure and higher quantity of aluminosilicate gel formation. Hence, the incorporation of silica fume significantly improved its acid resistance, thus LSG may have industrial applications concerning acid exposure.